An economic analysis of the value of grazing winter cover crops - Higgins, Todd R. (Kansas State University, 2017)
Cover crops can be used as forage for cattle and other grazing animals. This research investigated the net returns of using cover crops for forage or grazing under four scenarios. These scenarios were: 1) a mixed crop and livestock producer who owns a herd of cattle and has both dry or pregnant cows and weaned calves available to graze corn stover and cover crops; 2) a crop farmer who purchases stocker cattle for the purpose of grazing the cover crop and corn stover; 3) a crop farmer who leases out a corn stover and cover crop field to a livestock producer (and who provides value-added services to the livestock producer for a fee); and 4) an integrated operation with crops and cattle where cover crops are not grown and hay is fed to cattle during the winter months. Each of these scenarios had different budgets, risks, and profit potentials. The research aimed to address the risks and profit potentials for each scenario. The stocking density was initially set at three cows and 31 steers for a period of 90 days, and alternatively, three cows and 25 steers for a period of 120 days. Two sets of cattle pricing data were used: the average historical prices from 1992 to 2011 and reported prices from a regional stockyard for the period of November 2016 to March 2017. The results showed that the initial stocking densities used for scenarios one and two were too low to provide profitable net returns regardless of pricing data used. Net returns for scenario three were also not profitable based on the services rendered and the management fee charged. Scenario four was profitable on one occasion. November steers with a 500 lb. average starting weight fed hay and concentrate for 120 days resulted in a positive net return of $375. A second analysis was done using stocking rates of 50, 75, or 100 steers to determine if increasing stocking density would result in a positive net return using only the 2016/2017 pricing data and only evaluating net returns on 2.0 and 2.5 lbs. of average daily gain. Positive net returns were achieved at various start weights and average daily gain rates at stocking rates of 75 and 100 animals. No positive net returns were realized at the stocking rate of 50 animals/100 acre field. The management fee charged for providing management services under scenario three was adjusted based on stocking densities to determine if a positive net return could be achieved at the set fee rate of $0.875/head/day. At that rate, no stocking rate resulted in a positive net return. Using the cost data, less the $900 field lease income, a breakeven pricing point for the management fee was determined for each stocking density and grazing duration within the scenario. Management of cost factors to achieve greater chances of profitability and additional research needs are discussed.
Keywords: Cover crops; Soil health; Corn stover; Integration; Economic analysis